Attitudes of Slovenian students towards whole-body donation, organ donation, and the use of donated bodies in medical education - Žiga Šink; Gašper Tonin; Nejc Umek; Erika Cvetko (BMC Medical Education)
Abstract Background Anatomical dissection of whole bodies donated for teaching and research purposes remains a cornerstone of medical education. However, evolving sociocultural and ethical landscapes have historically influenced this practice, necessitating ongoing research to inform and enhance donation programs. This study examines the Slovenian students’ attitudes and factors influencing their decision-making regarding body and organ donation for medical education. Materials and Methods An anonymous cross-sectional cohort study was conducted at the University of Ljubljana using a 28-item questionnaire to assess student attitudes toward post-mortem whole-body and organ donation, as well as their perceptions of anatomical dissection in medical training and research. A five-point Likert scale was employed to evaluate attitudinal responses and identify underlying influencing factors. Results Analysis of 1528 student responses revealed significant differences in attitudes toward body and organ donation based on religious affiliation and anatomy course completion. Catholic students exhibited statistically lower levels of support and registration for donation compared to agnostic and atheist students (p < 0.001). A willingness to donate their bodies for teaching and research purposes was reported by 33.1% of participants. Notably, 26.3% would recommend whole-body donation to a family member, 27.9% to a friend, and 31.8% to a member of the general public. Students who had completed an anatomy course demonstrated a significantly higher likelihood of registering for organ donation (p = 0.003), yet were less inclined to donate their bodies for teaching and research due to concerns regarding the treatment of donated bodies. Conclusion Despite general support for organ and body donation, registration rates among Slovenian students remain low, including among those exposed to anatomy courses. We propose integrating end-of-life education, humanistic perspectives, and donor commemorative ceremonies into medical curricula to foster trust, ethical awareness, and advocacy for donation.